2010
DOI: 10.1016/j.jacc.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein and Coronary Heart Disease

Abstract: Coronary heart disease remains a major cause of worldwide morbidity and mortality despite therapeutic advances that control many risk factors such as low-density lipoprotein cholesterol to levels lower than previously possible. Population studies have consistently demonstrated an inverse association between high-density lipoprotein cholesterol (HDL-C) levels with the risk of coronary heart disease. As a result, HDL-C is gaining increasing interest as a therapeutic target. In this review, we explore the protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 281 publications
1
129
2
4
Order By: Relevance
“…This model is in apparent contradiction with data from large clinical trials that show a modest, but significant, increase in plasma HDL-cholesterol levels in patients treated with statins (recently reviewed in ref. 32). Interestingly, these latter studies show great variability between individuals, and the effects of some statins on HDL-cholesterol are not always dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…This model is in apparent contradiction with data from large clinical trials that show a modest, but significant, increase in plasma HDL-cholesterol levels in patients treated with statins (recently reviewed in ref. 32). Interestingly, these latter studies show great variability between individuals, and the effects of some statins on HDL-cholesterol are not always dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Although statin therapy led to a reduction in total cholesterol, the low HDL cholesterol reversed only following liver transplantation. Multiple studies in healthy subjects have demonstrated the predictive importance of low HDL cholesterol in future cardiac and cerebrovascular outcome (Natarajan et al 2010). Indeed a recent consensus statement on defining the metabolic syndrome has used a cut-off of less than 1.3 mmol/L as abnormal in a female population (Alberti et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, during cardiovascular inflammation cholesterol esters may be transferred from HDL to apolipoprotein B-containing particles, such as LDL or VLDL [62]. Trapping of apolipoprotein B containing particles within the arterial wall is unquestionably the essential initiating event for the development of complex atherosclerotic lesions [50].…”
Section: The Immune Phenotype: the Pathological Management Of Fatmentioning
confidence: 99%